Letter (copy) : Persecutions in Spain - Citrine, Walter, 1887-1983
013-0080-001 International, WMC/WJB/DT/926. 9th May, 1940. Mr. W. Carrillo, Bayswater Hotel, Bayswater Road, LONDON. W.2. Dear Mr. Carrillo, PERSECUTIONS IN SPAIN. We have delayed answering your last letter of the 29th of April in the hope that some news would have come to hand by now giving us ground for hope that attention was at last being given by the Spanish authorities to representations that have been made to them on behalf of the Trade Union leaders in their country. On receipt of your communication we immediately submitted again a request that everything should be done in order to secure the freedom of Caballero's son and to save Rafael Henche from execution. We regret to say that no definite information has yet come to hand as to the result of the steps we have taken and we can only express the hope that now some considerable time has elapsed since the Franco Government seized power the latter will have become more humanely disposed and will exercise clemency in dealing with their prisoners. Yours sincerely, General Secretary. 292/946/13/80